Penerapan Media Gambar dalam Meningkatkan Kemampuan Membaca Siswa Sekolah Dasar - Dina Liana; Siska Ashari (Universitas Islam Negeri Imam Bonjol Padang, 2023)
In carrying out the learning process in grade 1 elementary school, of course, there are problems, especially in reading skills, but these problems can be solved by means of a teacher's creativity. The purpose of this study was to find out the increase in students' reading skills after applying media images for grade 1 students of elementary school 007 Kotabaru Reteh, Keritang District. The method used by researchers is a qualitative and quantitative method with the type of classroom action research carried out in 3 cycles. The results obtained were that students' reading skills increased after applying learning media with pre-cycle values of 50.5%, cycle 1 57.9%, cycle 2 75.5% and cycle 3 88.9% so it can be concluded that reading ability can increased after applying media images to grade 1 elementary school students.